Pengaruh Literasi Keuangan dan Penggunaan Fintech Terhadap Kinerja Keuangan Serta Pengelolaan Keuangan Sebagai Variabel Moderasi (Studi Pada Star Seller Marketplace Shopee di Kota Malang Tahun 2025) - Musyaffik Rifqi Ahmada; Ayub Wijayati Septa Pradana (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid growth of e-commerce in Indonesia, particularly among Shopee Star Sellers in Malang City, which have high transaction volumes, is not necessarily accompanied by optimal monetary results. This study aims to examine the impact of financial literacy and the use of financial technology about financial performance, with financial Using management as a moderating factor. This study used a quantitative research method, collecting data using a questionnaire from 140 respondents using a purposive sampling technique. The results show that financial performance is positively and significantly impacted by financial knowledge. Financial performance has also been shown to be positively and significantly impacted by the usage of financial technology. The impact of financial literacy on financial performance has not, however, been shown to be mitigated by financial management. Additionally, it has not been demonstrated that financial management can mitigate the impact of financial technology use on financial performance. These findings show that using financial technology and raising financial literacy both directly enhance financial performance. The study concludes that while financial management does not function as a moderating variable in this research model, financial literacy and the usage of financial technology are the primary determinants in increasing financial performance.